Traumatic Coxofemoral Luxation in Dysplastic Dogs Managed with a Triple Pelvic Osteotomy: Results in four Dogs - Murphy, S. T.; Lewis, D. D.; Kerwin, S. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
Triple pelvic osteotomy (TPO) was used in the treatment for traumatic coxofemoral luxations in four adult, large breed dogs with hip dysplasia. Initial closed reductions failed in three and one dog had an initial closed reduction and subsequent open reduction of the coxofemoral luxation that failed. Hip dysplasia was thought to be a prominent factor contributing to the reluxation. TPO successfully maintained reduction of the coxofemoral luxation in all of the dogs. An increase in dorsal acetabular coverage of the femoral head following TPO was demonstrated by an increased Norberg angle. The improved congruency was thought to maintain reduction of the femoral head in the acetabulum and decrease stresses on the joint capsule, allowing healing to occur. Long-term (median: 343, mean ± SD: 406 ± 226 days follow-up) function of the affected limb was comparable to the contralateral limb. Three of the four dogs did not have radiographic progression of coxofemoral degenerative joint disease of the affected joint and differences in the progression of degenerative joint disease were not evident between the affected and the contralateral coxofemoral joint. A decrease in abduction and external rotation and an increase in internal rotation following TPO was noted in the affected coxofemoral joint. Our results establish the utility of this procedure in dysplastic dogs with traumatic coxofemoral luxations.Triple pelvic osteotomy used in the treatment for traumatic coxofemoral luxation in four adult, large breed dogs with hip dysplasia successfully maintained reduction and resulted in satisfactory limb function in all patients.
Keywords: Coxofemoral luxation; triple pelvic osteotomy